Hydrodynamic Model Simulation at the Port of Tanjung Rhu Belitung - Sujantoko; Pramudya Adhi Pangestu; Dony Saputra; B. P. Putra Ekianto; Hasanudin Ekianto; Nani Kurniati; Rindi Kusumawardhani; Dody Hartanto (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Ports around Belitung Island have an essential role in supporting inter-island shipping activities, which positively impact economic growth. So that predictions to find out the condition of the waters need to be made early to anticipate disruption to the ship's shipping lanes. This study's prediction of these waters was carried out with a hydrodynamic model. Model accuracy (calibration) compares model results with survey data. Based on several iterations, the tidal model and current velocity are obtained with an accuracy rate of 5% and 7%, respectively. These results indicate the model's relatively good level of accuracy because it is below 10%. The model results also found that current velocity and wave height are always higher during high tide conditions than during low tide. In addition, along the Tanjung Rhu shipping channel, the current speed at point A1 experiences a significant difference during high tide conditions, namely 0.285 m/s at high tide, 0.102 m/s at low tide, 0.072 m/s at low tide, and 0.033 m/s s when heading for high tide, because of the narrowing of the water area due to the crush of two landmasses. In addition, areas far from shipping lanes (A1 and A2) have the lowest wave height compared to areas close to shipping lanes (A3). Because the surrounding land slightly covers the two points (A1 and A2), the wave height is smaller than point A3 in more open waters.